A new monoclinic polymorph of N-(3-methylphenyl) ethoxycarbothioamide: Crystal structure and Hirshfeld surface analysis - Mukesh M,; Yeo, Chien Ing *; Tiekink, Edward R. T. * (International Union of Crystallography, 2017)
The title compound, C10H13NOS, is a second monoclinic polymorph (space group P21/c, Z′ = 2) of the previously reported C2/c (Z = 1) polymorph [Tadbuppa & Tiekink (2005). Z. Kristallogr. New Cryst. Struct. 220, 395–396]. Two independent molecules comprise the asymmetric unit of the new polymorph and each of these exists as a thioamide–thione tautomer. In each molecule, the central CNOS chromophore is strictly planar [r.m.s. deviations = 0.0003 and 0.0015 Å] and forms dihedral angles of 6.17 (5) and 20.78 (5)° with the N-bound 3-tolyl rings, thereby representing the major difference between the molecules. The thione-S and thioamide-N—H atoms are syn in each molecule and this facilitates the formation of an eight-membered thioamide {...SCNH}2 synthon between them; the dimeric aggregates are consolidated by pairwise 3-tolyl-C—H...S interactions. In the extended structure, supramolecular layers parallel to (102) are formed via a combination of 3-tolyl-C—H...π(3-tolyl) and weak π–π interactions [inter-centroid distance between 3-tolyl rings = 3.8535 (12) Å]. An analysis of the Hirshfeld surfaces calculated for both polymorphs reveals the near equivalence of one of the independent molecules of the P21/c form to that in the C2/c form.